Cumulative Live Birth Rates According to Maternal Body Mass Index After First Ovarian Stimulation for in vitro Fertilization: A Single Center Analysis of 14,782 Patients - Xia Xue; Xia Xue; Wenhao Shi; Hanying Zhou; Li Tian; Zhenghao Zhao; Dangxia Zhou; Juanzi Shi (Frontiers in Endocrinology, 2020)
Objective: To investigate the cumulative live birth rates (CLBR) according to body mass index (BMI) in women undergoing their first in vitro fertilization (IVF).Design: Retrospective cohort analysis.Setting: An IVF clinic in a public hospital.Patients: This is a retrospective study of 14,782 patients undergoing their first fresh IVF cycles and subsequent frozen embryo transfers in our clinic from January 2014 to January 2017. The follow-up for CLBR continued until January 2019. Patients with a BMI <18.5 kg/m2 were considered to be underweight and those with a BMI > 24 kg/m2 were considered to be overweight. Patients with a BMI ≥ 28 kg/m2 were considered to be obese.Intervention(s): None.Primary Outcome Measure: The primary outcome was cumulative live birth rate (CLBR).Result(s): This study illustrated the “inverted U shape” associations between body weight and IVF outcome (CLBR). The turning points in threshold analysis, as found by an automatic search, were BMIs of 18.5 and 30.4 kg/m2. The main finding of this retrospective data analysis is that the CLBR increased in underweight women, plateaued for normal weight and overweight women with a BMI between 18.5 and 30.4 kg/m2, and decreased in obese women.Conclusion(s): The data suggested an “inverted U shape” association between BMI and CLBR. The CLBR increases in underweight women, plateaus in normal weight and overweight women, and then decreases in obese women.